2020
DOI: 10.1101/2020.09.14.296970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking strains predicts personal microbiomes and reveals recent adaptive evolution

Abstract: An individual’s microbiome consists of a diverse set of bacterial strains that encode rich information on its colonization and evolutionary history. Here, we introduce a versatile and straightforward reference-based strain tracking approach (StrainTrack) that determines whether distinct metagenomes carry closely-related strains based on gene presence and absence profiles. We show that StrainTrack can predict whether two metagenomes originate from the same donor via counting the number of species sharing closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As time progresses and purifying selection continuously operates, the d N /d S ratio decreases [14] [19] [22]. However, multiple studies have observed genome-wide values of d N /d S above 1 in these same microbial systems, with values substantially above 1 in key genes, which are simply unaccounted for in the purifying model [19] [20] [23] [24] [25].…”
Section: Introductionmentioning
confidence: 99%
“…As time progresses and purifying selection continuously operates, the d N /d S ratio decreases [14] [19] [22]. However, multiple studies have observed genome-wide values of d N /d S above 1 in these same microbial systems, with values substantially above 1 in key genes, which are simply unaccounted for in the purifying model [19] [20] [23] [24] [25].…”
Section: Introductionmentioning
confidence: 99%
“…The gut of nearly every individual is colonized with organisms from the phyla Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria (Qin et al, 2010). Despite the universality of these four core phyla, the gut microbiome harbors extraordinary interpersonal complexity, particular at the strain level (Eckburg et al, 2005;Faith et al, 2020Faith et al, , 2013Olm et al, 2021;Schloss et al, 2014;Zhao et al, 2020). The proximity of gut bacteria to the host presents a unique challenge for the immune system, which must maintain tolerance to the resident microbiota while remaining poised to defend against infectious insults.…”
Section: Introductionmentioning
confidence: 99%
“…Improving our fundamental understanding of these behaviors depends on detailed knowledge of the genes and pathways specific to particular microbes ( 22 ); however, elucidating this information can present considerable challenges where taxa are only known at the species level, obscuring strain-level differences. Individual microbes from the same strain from a single microbiome largely share the same genome ( 12 , 23 ); therefore, a substantial improvement in understanding would be provided by high-quality genomes resolved to the strain level from a broad range of microbial taxa within a given community.…”
mentioning
confidence: 99%